2012
DOI: 10.1089/jop.2011.0165
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Masked Randomized Crossover Study Comparing the Effect of Latanoprost/Timolol and Brimonidine/Timolol Fixed Combination on Intraocular Pressure and Ocular Blood Flow in Patients with Primary Open-Angle Glaucoma or Ocular Hypertension

Abstract: In the present study, a 6-week treatment with LT or BT was equally effective in reducing IOP. In addition, none of the administered drugs induced a significant effect on ocular blood flow parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Other fixed combinations produced and commercialized by Allergan are 0.2% brimonidine-0.5% timolol (BRIMOTFC, Combigan ® ) and 0.03% bimatoprost-0.5% timolol (BIMATOFC, Ganfort ® ). Different studies stress the efficacy and safety of BRIMOTFC versus the unfixed components or another fixed combination [2][3][4][5][6][7][8][9]. Other papers underline the efficacy and safety of DTFC, even three times a day [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Other fixed combinations produced and commercialized by Allergan are 0.2% brimonidine-0.5% timolol (BRIMOTFC, Combigan ® ) and 0.03% bimatoprost-0.5% timolol (BIMATOFC, Ganfort ® ). Different studies stress the efficacy and safety of BRIMOTFC versus the unfixed components or another fixed combination [2][3][4][5][6][7][8][9]. Other papers underline the efficacy and safety of DTFC, even three times a day [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Monotherapy with timolol decreases aqueous humor production to reduce IOP, and protects retinal ganglion cells in a rat glaucoma model. 11,12) Latanoprost and timolol in a fixed combination greatly reduced IOP in patients with primary open angle glaucoma in a double masked, randomized clinical trial.12) The latanoprost/timolol combination provides a greater ocular hypotensive effect than monotherapy with latanoprost or timolol.13) Although the greater ocular hypotensive effect of combination is well-understood, it is not known if the combination has a greater neuroprotective effect than either drug alone.In the present study, we have investigated the neuroprotective effects of a latanoprost/timolol combination on retinal damage and the mechanism of the protective effect of this combination of drugs in vitro. …”
mentioning
confidence: 99%
“…Monotherapy with timolol decreases aqueous humor production to reduce IOP, and protects retinal ganglion cells in a rat glaucoma model. 11,12) Latanoprost and timolol in a fixed combination greatly reduced IOP in patients with primary open angle glaucoma in a double masked, randomized clinical trial.…”
mentioning
confidence: 99%
“…Only one study comparing LTFC to 0.2% Brimonidine/0.5% timolol (BTFC) met the criteria, so we included that study in the system review but did not conduct a meta-analysis. This is a moderate study involving 18 patients [28]. The results showed that there was no significant difference in reductions in the mean diurnal IOP as of 1.5 months of treatment (MD = 0.50 mmHg; P = 0.57).…”
Section: Effects Of Interventionsmentioning
confidence: 86%